Comunicación comunitaria y su impacto en el desarrollo social del barrio Vinchoa Central, año 2023 - Enríquez García, Evelyn Adriana (2024)
The present research work is to design communication strategies that help Community Communication and its impact on the Social Development of the Vinchoa Central neighborhood, year 2023, this study aims to strengthen communication in the community and contribute to the social development of the location. Lack of communication is a major factor that leads to divisions in organizations, groups of individuals, communities, etc. This creates a problem for local residents. Community leaders, as well as social actors, must be able to guide community members to achieve social changes and achieve the desired goals and projections. Communities must develop community activities that involve everyone, promoting the active participation of residents. The types of research used are: descriptive, field, bibliographic, with qualitative, quantitative research methods; as techniques and instruments for data collection, interviews and surveys aimed at the residents of the Vinchoa Central neighborhood and the Sociologist Oswaldo González.